An improved machining process of polished silicon using nano powder mixed micro-wire electro discharge machining - Jarin, Sams; Saleh, Tanveer; Bhuiyan, Moinul; Muthalif, Asan G. A.; Ali, Mohammad Yeakub (2017)
Micro Wire Electro Discharge Machining (μ-WEDM) is a non-conventional promising machining process which is used mainly to machine complex shaped parts for research and industrial applications. However, for machining semiconductor material with high resistivity like silicon (Si) requires some special techniques to produce better machining stability during the μ-WEDM operation process. One of such ways is to coat Si temporarily with a conductive coating (such as gold or copper) that enhances the discharge current flow through Si workpiece. In this study, temporarily gold coated silicon wafer has been machined by μ-WEDM where workpieces were submerged into the nano powder mixed dielectric medium. This causes the dielectric strength of the medium to be lowered and machining can be carried out more smoothly. The main aim of this work is to identify the effects of nano powder assisted μ-WEDM operation on gold coated silicon wafer. The machining efficiency of the gold (Au) coated Si wafer were determined by the average surface roughness (ASR), material removal rate (MRR) and spark gap (SG). Based on the experimental observation, it has been found that for most of the experiments, the MRR of Si were higher for nanopowder assisted WEDM operation (almost 39% improved). The SG was however, increased (from 2% to159% range) when nanopowder was used in the dielectric medium. Finally, the ASR of the WEDMed surface were observed to be significantly lower (from 4% to 121% maximum) for the nano powder mixed dielectric medium than pure dielectric medium.